Skilled migration in latin america in the United States and Chile: determining finding work - González Becerril, Juan Gabino; Canales Cerón, Alejandro; Cruz Piñeiro, Rodolfo; Ocampo González, Melina (Universidad Autónoma del Estado de México, 2017)
This paper has a double purpose, on the one hand, reviewing the most important factors in explaining the employment of qualified Latin American immigrants in the United States three times, 2000, 2009 and 2013. Moreover, verify the determinants the employment of Latin American immigrants in Chile in 2013. to determine which variables have the greatest weight in the labor incorporation is used as a source of information the American Community Survey, 2000, 2009 and 2013 (ACS) and the Survey of National Socioeconomic Characterization, 2013 (CASEN) and to test the hypothesis underutilization of the capabilities of highly educated immigrants in the places of the model binary logistic regression based on comparative explanation considering the dimension of human capital, demographic and used context. Thus posed the following question: What factors have greater weight in explaining the employment of Latin American immigrants in the United States? What are the differences in the weight of the variables in the US labor market and the likelihood of Chilean inserted into an unskilled occupation. The main argument is greater underutilization of the capabilities of skilled workers in the labor market.